The Effects Of Remunerations, Inspections, Work Fines On Work Discipline Study PT Kebon Agung PG Trangkil Pati District - Aditya Angger Wibowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to investigate how PG Trangkil Pati workers' work discipline is affected by pay, inspections, and penalties. All PG Trangkil Pati employees that were chosen using the proportionate random sample method provided the data for this study. 194 employees in all, with 130 replies in the sample. A questionnaire is used to collect data. Following data collection, multiple linear regression analysis is performed with the aid of the SPSS application. According to the study's findings, which are partially supported by the 5, 886> 1, 979, employee work discipline is positively and significantly impacted by compensation. 4. 316> 1. 979 shows that inspections have a good and significant impact on employee work discipline. The 4. 688> 1. 979 shows that work penalties have a favorable and substantial influence on employee work discipline to a partly extent. The result of 46, 701> 2. 68 indicates that employee work discipline is positively and significantly impacted by compensation, inspections, and work penalties all at the same time